Prevalence of Anemia in A Sample of Elderly Subjects from Tripoli, Libya - Eman Abdulwahed; Heyam Rhoma; Maram Sultan (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and Aims: Anaemia is a common in elderly and its incidence increases in the last few decades. While most literature has focused on children, women of childbearing age, and pregnant women, data for the elderly population are relatively rare. The purpose of this study was to determine the prevalence, severity of anaemia, and its association with demographic and clinical characteristics in a representative sample of elderly people from Tripoli-Libya. Methods. A total of 81 adults aged 60 years and above were enrolled in this study. A structured questionnaire was used to capture sociodemographic and clinical characteristics. Blood samples were collected, and a complete blood count were measured to assess anemia and its severity in all participants. The data was analyzed using (SPSS) software, version 20. Frequencies, proportions, and rates of the given data for each variable was calculated. The differences between the groups with and without anemia were analyzed using chi-squared test. Statistical significance was defined as a p-value < 0.05. Results. The overall prevalence of anaemia in the elderly population was 44%. The prevalence of anemia was higher in women than men (51% vs 36%). The prevalence of anemia was higher in windowed, divorced and married than in single individuals 79%, 37%, 25%, respectively (p value 0.014). The prevalence of anemia was higher in elderly who have medical history than who with none medical history (p-value =0.002). Elderly who has diabetes and hypertension showed a trend towards an increased prevalence of anemia (p-value = 0.032). Moderate anaemia was found in 26 (33%) anaemic participants followed by severe anaemia in 9 (11%) anaemic participants. Moderate anaemia was the most common type of anaemia among elderly. Conclusion. The current outcomes exhibited a relatively high prevalence of anemia in elderly. Therefore, further examination of the cause of anemia and the completion of treatment might assist to improve clinical conditions in the elderly population.